“Turn on” electron-transfer-based selective detection of ascorbic acid via copper complexes immobilized on glass - Singh, Vikram; Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael; Gupta, Tarkeshwar (The analyst, 2012)
“Turn-on” optical detection of parts-per-million (ppm) levels of ascorbic acid (AA) in water has been determined using a redox-active monolayer on glass.
Gesehen am 14.08.2019